The effects of hard and soft tissue grafting and individualization of healing abutments at immediate implants: an experimental study in dogs - Thoma, Daniel S. (J Periodontal Implant Sci, 2019)
PURPOSE: To evaluate the effects of intra-alveolar socket grafting, subepithelial connective tissue grafts, and individualized abutments on peri-implant hard and soft tissue outcomes following immediate implant placement. METHODS: This randomized experimental study employed 5 mongrel dogs, with 4 sites per dog (total of 20 sites). The mesial roots of P3 and P4 were extracted in each hemimandible and immediate dental implants were placed. Each site was randomly assigned to 1 of 4 different treatment groups: standardized healing abutment (control group), alloplastic bone substitute material (BSS) + standardized healing abutment (SA group), BSS + individualized healing abutment (IA group), and BSS + individualized healing abutment + a subepithelial connective tissue graft (IAG group). Clinical, histological, and profilometric analyses were performed. The intergroup differences were calculated using the Bonferroni test, setting statistical significance at P<0.05. RESULTS: Clinically, the control and SA groups demonstrated a coronal shift in the buccal height of the mucosa (0.88±0.48 mm and 0.37±1.1 mm, respectively). The IA and IAG groups exhibited an apical shift of the mucosa (−0.7±1.15 mm and −1.1±0.96 mm, respectively). Histologically, the SA and control groups demonstrated marginal mucosa heights of 4.1±0.28 mm and 4.0±0.53 mm relative to the implant shoulder, respectively. The IA and IAG groups, in contrast, only showed a height of 2.6 mm. In addition, the height of the mucosa in relation to the most coronal buccal bone crest or bone substitute particles was not significantly different among the groups. Volumetrically, the IA group (−0.73±0.46 mm) lost less volume on the buccal side than the control (−0.93±0.44 mm), SA (−0.97±0.73 mm), and IAG (−0.88±0.45 mm) groups. CONCLUSIONS: The control group demonstrated the most favorable change of height of the margo mucosae and the largest dimensions of the peri-implant soft tissues. However, the addition of a bone substitute material and an individualized healing abutment resulted in slightly better preservation of the peri-implant soft tissue contour.